Risk factors for stunting children in urban areas: case-control study in Putrajaya - Salleh, Ruhaya; Ahmad, Mohamad Hasnan; Mohd Zaki, Nor Azian; Mohd Sallehuddin, Syafinaz; Baharudin, Azli; Amali, Khairul Hasnan; Abu Saad, Hazizi; Poh, Bee Koon (BioMed Central, 2026)
A well-developed city, Putrajaya, was listed as having one of the highest stunting rates in 2016. This study examines determinants of stunting among children under five in Putrajaya. A case-control study was conducted between September 2018 and January 2019. Note that 8261 children aged 6–59 months were screened in preschools and government health clinics. From these, 386 stunted children (cases) and 386 normal children (controls) were randomly selected and matched by sex and age group. Data were obtained from face-to-face interviews with parents on sociodemographics, health, medical history, knowledge, and practice regarding children’s feeding, dietary behaviour, food security, and physical activity. Anthropometric measurements, finger pricks for haemoglobin level, and a self-administered 3-day food diary were also collected. Multiple logistic regression was performed to identify the factors associated with stunting. Results. A total of 386 stunted and 386 normal children were recruited. The final model found that mid-parental height (< 150 cm)(aOR = 3.8), low household income (B40) (aOR = 3.4), Low Birth Weight (LBW) (aOR = 3.1), and use of pacifiers were about three 3 times higher odds of associated with stunting. Stunting was significantly associated with Intra-Uterine Growth Restriction (IUGR) (aOR = 7.9). Other factors linked to the outcome were low maternal education, paternal unemployment, childhood anaemia, bottle feeding, poor dietary diversity, and care by babysitters. Stunting in this urban population reflects biological (genetic load, IUGR, LBW) and modifiable factors (feeding practices, income, parental education). Without early intervention, the consequences extend to impaired cognitive development, reduced school achievement, lower adult productivity, and increased chronic disease risk. Findings underscore the urgency of targeted interventions in urban Malaysia, aligning with the and Malaysia’ goal to reduce stunting below 11%.